2022
DOI: 10.1007/s00464-022-09692-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound guided gastrojejunostomy in the treatment of gastric outlet obstruction: multi-centre experience from the United Kingdom

Abstract: Background Endoscopic ultrasound guided gastrojejunostomy (EUS-GJ) with lumen apposing metal stents has recently emerged as a viable option, as an alternative to surgical gastrojejunostomy and endoscopic enteral stenting, for managing gastric outlet obstruction (GOO). We aim to perform a retrospective analysis of the efficacy, safety and outcomes of EUS-GJ performed at three tertiary institutions in the United Kingdom. Methods Consecutive patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Current studies recognize EUS-GE as a promising but highly challenging therapeutic option for GOO, performance of which should be limited to high-volume expert centers [1,9]. The procedure consists of several technically demanding steps, including locating the jejunum endosonographically and ensuring ▶ Original article ▶ proper LAMS deployment and placement, all while overcoming the mobility of the small bowel [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies recognize EUS-GE as a promising but highly challenging therapeutic option for GOO, performance of which should be limited to high-volume expert centers [1,9]. The procedure consists of several technically demanding steps, including locating the jejunum endosonographically and ensuring ▶ Original article ▶ proper LAMS deployment and placement, all while overcoming the mobility of the small bowel [10].…”
Section: Discussionmentioning
confidence: 99%
“…Electrocautery-enhanced LAMS enable a one-step approach for target loop puncture, anastomosis dilation, and stent deployment, and for this procedure, their freehand use appears to be most frequent [5,8,1]. Nevertheless, despite several reviews recommending the freehand approach [8,9,13], a trend supported by our survey results, a substantial number of surveyed experts continued to puncture the target loop for reasons such as the aspiration of dyed fluid to confirm target loop etiology and the injection of additional fluid for further distension. Given that the most commonly reported EUS-GE-related AE is stent misdeployment likely stemming from the inherently mobile and contractile nature of the small bowel, it is unlikely a single standardized protocol will completely eliminate AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Akin to the surgical procedure, EUS can be used to create anastomosis, or gastrojejunostomy (EUS–GJ), in patients with unresectable pancreatic cancer between the gastric lumen and a downstream loop of small bowel beyond the point of obstruction. This is typically performed by distending the downstream bowel with copious fluid, followed by the endosonographic visualization of the dilated loop of bowel from the gastric lumen and deploying a lumen-apposing metal stent (LAMS) to create an anastomosis [ 92 ]. Clinical success rates between endoscopic and surgical methods are similar (84% for EUS–GJ, 87% for enteral stenting, and 90% for surgical gastrojejunostomy), with significantly fewer complications with the endoscopic modalities (12% for EUS–GJ, 11.66% for enteral stenting, and 41% for surgical gastrojejunostomy) [ 93 , 94 , 95 ].…”
Section: Eus-guided Gastrojejunostomymentioning
confidence: 99%
“…On W et al. ( 51 ) analyzed patients with gastric outlet obstruction who underwent continuous endoscopic ultrasound-guided gastroenterostomy (EUS-GJ) between August 2018 and March 2021, and found that the success rate of surgery was as high as 92%, the mean score of the gastric outlet obstruction scoring system was improved compared with SGJ (2.52 vs 0.68, p<0.01), and only 8% of patients reported adverse events, all of which were due to improper stent deployment and incurred gastric defect that requires endoscope to repair. This indicated that EUS-GJ could effectively improve the symptoms of patients with gastric outlet obstruction, and was safer and more efficient.…”
Section: Gastrojejunostomymentioning
confidence: 99%